Validation of a real-time quantitative polymerase chain reaction method for the quantification of 3 survivin transcripts and evaluation in breast cancer tissues - Pavlidou, A.; Kroupis, C.; Goutas, N.; Dalamaga, M; Dimas, K. (Clin.Breast Cancer, 2014)
BACKGROUND: Survivin is a novel antiapoptotic gene, which is a member of the inhibitor of apoptosis protein (IAP) family. Recently, 3 splice variants of this gene were cloned and characterized. This study aimed to validate a sensitive and specific method for the detection of survivin variants in breast cancer. METHODS: Real-time quantitative polymerase chain reaction (qPCR) was performed on the cDNA with a reverse primer specific for each splice variant and a pair of common hybridization probes. RESULTS: The expression of wild-type survivin was significantly correlated with survivin-2b, survivin-DeltaEx3, and the ratio of survivin-DeltaEx3 to wild-type survivin (P < .001). The ratio of survivin-2b to wild-type survivin was strongly associated with the ratio of survivin-DeltaEx3 to wild-type survivin (P < .001). There was a strong positive association between the grade of the tumor and survivin-2b mRNA, survivin-DeltaEx3 mRNA, and the ratio of survivin-DeltaEx3 to wild-type survivin mRNA (P < .05). The ratio of survivin-2b to wild-type survivin was significantly associated with the presence of estrogen receptors (P = .05). CONCLUSION: Our validated data suggest that survivin isoforms may be related to clinicopathological features and could be used as molecular prognostic tools or as new therapy targets
DA - 20140318 IS - 1938-0666 (Electronic) IS - 1526-8209 (Linking) LA - eng PT - Journal Article PT - Validation Studies RN - 0 (BIRC5 protein, human) RN - 0 (Inhibitor of Apoptosis Proteins) RN - 0 (Protein Isoforms) SB - IM
Keywords: Breast Neoplasms; Female; Gene Expression Regulation,Neoplastic; genetics; Humans; Inhibitor of Apoptosis Proteins; Neoplasm Grading; Neoplasm Invasiveness; pathology; Prognosis; Protein Isoforms; RNA Splicing; Survival Rate